2013
DOI: 10.5513/jcea01/14.2.1229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of behaviour of Holstein-Friesian and Simmental bulls on semen quality

Abstract: The aim of the study was to determine the relationship between the behaviour of Holstein-Friesian and Simmental bulls and the quality of their semen. A total of 76 breeding bulls of the Holstein-Friesian and dual-purpose Simmental breeds were investigated. Analysis was made of the response of bulls to humans and other bulls, facial hair whorl position and length, scrotal circumference, and semen characteristics (mean ejaculate volume, mean sperm concentration, and sperm wave motion). The age and breed of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The overall correlation coefficient results of the scrotal circumference and semen volume are in the moderate category (r = 0,328; p < 0,05). This result is in line with Devkota (2008), Adamczyk et al (2013), Prayogo et al (2013), Muthiapriani et al (2019), and Mahendra et al (2022, who reported that there was a positive relationship between scrotal circumference and semen concentration with moderate category. However, unlike the research of Teixeira et al (2011), Gopinathan et al (2016), and Indriastuti et al (2020, which found a negative relationship between the two variables.…”
Section: Relationship Between Scrotal Circumference and Semen Concent...supporting
confidence: 79%
“…The overall correlation coefficient results of the scrotal circumference and semen volume are in the moderate category (r = 0,328; p < 0,05). This result is in line with Devkota (2008), Adamczyk et al (2013), Prayogo et al (2013), Muthiapriani et al (2019), and Mahendra et al (2022, who reported that there was a positive relationship between scrotal circumference and semen concentration with moderate category. However, unlike the research of Teixeira et al (2011), Gopinathan et al (2016), and Indriastuti et al (2020, which found a negative relationship between the two variables.…”
Section: Relationship Between Scrotal Circumference and Semen Concent...supporting
confidence: 79%
“…Libido of the breeding bull was measured according to Adamczyk et al (2013) (Table 1). 2 Weak sex drive.…”
Section: Measurement Of Libidomentioning
confidence: 99%
“…Similarly, variation has been observed among bulls on sperm concentration by various researchers. For instance, Adamczyk et al, (2013) and Alemayehu and Tena (2015) at different places reported significant differences in semen concentrations between different breeds. A lack of significant variation has been reported as well by several researchers including Boujenane and Boussaq (2014).…”
Section: Discussionmentioning
confidence: 97%